Minapolitan Program Implementation In Kalanganyar Village, Sedati District, Sidoarjo Regency - Susi Hardjati; Edo Wahyudi, Kalvin; Prathama, Ananta (International Journal of Educational Research & Social Sciences, 2022)
The blue revolution, a key marine and fisheries-based economic development strategy, has its primary manivestation in the Minapolitan initiative. The Ministry of Maritime Affairs and Fisheries runs the Minapolitan program in a number of locales, including Kalanganyar Village, Sedati District, and Sidoarjo Regency. The purpose of this study is to evaluate how the Minapolitan program has been implemented in Kalanganyar Village. The Meter-Horn implementation model is the predominant theory employed, which includes six aspects: clarity of standards and policy objectives, adequacy of resources, quality of communication, environmental involvement, structural characteristics, and disposition of implementers. A qualitative methodology with a descriptive type is used in this investigation. Data were gathered using focus groups, interviews, document gathering, and observation. Using an interactive model for data analysis. The results showed that, in general, the implementation was quite optimal. However, four things need serious attention: the absence of technical guidelines for implementation, the low budget adequacy, the lack of staff for program implementation, and the lack of community involvement in infrastructure projects. These problems must be considered so that implementation can run optimally.